2022
DOI: 10.1021/acs.jpca.2c02435
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of Charge Transfer in the Emission Properties of Carborane–Fluorophore Systems: A TDDFT Investigation

Abstract: In this study, we performed a detailed investigation of the S 1 potential energy surface (PES) of o -carborane–anthracene ( o -CB– Ant ) with respect to the C–C bond length on o -CB and the dihedral angle between o -CB and Ant moieties. The effects of different substituents (F, Cl, CN, and OH) on carbon- or boron-substituted o -C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…o ‐Carboranes are also known to influence attached systems via their strong −I inductive effect, stabilizing the frontier orbitals [101–103] . We and others have shown that the coexisting LE and CT excited states can be connected by a low energy barrier and yet show very different geometries and orbital distributions [87,97–98,104–106] . In 1‐(pyrenyl‐2′‐yl)‐ o ‐carborane ( VI ), we were able to simulate and experimentally confirm a thermodynamic equilibrium between the LE and CT excited states by determining the relevant interconversion rates [87] .…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…o ‐Carboranes are also known to influence attached systems via their strong −I inductive effect, stabilizing the frontier orbitals [101–103] . We and others have shown that the coexisting LE and CT excited states can be connected by a low energy barrier and yet show very different geometries and orbital distributions [87,97–98,104–106] . In 1‐(pyrenyl‐2′‐yl)‐ o ‐carborane ( VI ), we were able to simulate and experimentally confirm a thermodynamic equilibrium between the LE and CT excited states by determining the relevant interconversion rates [87] .…”
Section: Introductionmentioning
confidence: 69%
“…[101][102][103] We and others have shown that the coexisting LE and CT excited states can be connected by a low energy barrier and yet show very different geometries and orbital distributions. [87,[97][98][104][105][106] In 1-(pyrenyl-2'-yl)-o-carborane (VI), we were able to simulate and experimentally confirm a thermodynamic equilibrium between the LE and CT excited states by determining the relevant interconversion rates. [87] Other pyrenyl-o-carboranes have received considerable attention as chromophores and show potential applications in photocatalysis.…”
Section: Introductionmentioning
confidence: 96%
“…However, some aryl- o -carboranes possessing little LE/ICT barrier 30 also showed moderate Φ PL values, suggesting there should be an additional factor relating to nonradiative decay from the ICT state to comprehend the overall PL process. 20…”
Section: Resultsmentioning
confidence: 99%
“…However, some aryl-o-carboranes possessing little LE/ICT barrier 30 also showed moderate F PL values, suggesting there should be an additional factor relating to nonradiative decay from the ICT state to comprehend the overall PL process. 20 Next, temperature-dependent PL spectra in CHCl 3 were collected for further investigation of the excited state (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation